Generation of 100 nJ pulse, 1 W average power at 2 [STIX]x03BCm from an intermode beating mode-locked all-fiber laser. (2019) - Zhang, Jiaji; Wu, Duanduan; Zhao, Ruwei; Wang, Rongping; Dai, Shixun
Abstract : We report on the investigation of intermode beating mode-locked (IBML) pulse generation in a simple all-fiber Tm ^3+ -doped double clad fiber laser (TDFL). This IBML TDFL is implemented by matching longitudinal-mode frequency between 793 nm laser and TDFL without extra mode locker. The central wavelength of 1983 nm, the fundamental pulse frequency of 9.6 MHz and the signal-to-noise ratio (SNR) of >50 dB are achieved in this IBML TDFL. With laser cavity optimization, the IBML TDFL can finally generate an average output power of 1.03 W with corresponding pulse energy of 107 nJ . These results can provide an easily accessible way to develop compact large-energy, high-power TDFLs.